(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
The phenomenon of advance and delay is one of the most prominent linguistic phenomena in the Arabic language. It denotes a deep understanding of language, a capacity for behavior, possession of reins, and good thinking through systems that reveal the beauty of language, in addition to being a phenomenon that carries in its folds meanings and connotations that the context of speech leads to. The research plan came in an introduction, an introduction, and two papers, the introduction was in explaining the importance of the topic, the reason for choosing, the methodology, and the research plan, while the prelude was in the concept of introduction and delay. The first topic was in a statement of the objection to the introduction and delay in the noun sentence by presenting the news to the subject, and providing the news of the suspicious letters in its name, so that the second topic would be in the viewer of introduction and delay in the actual sentence with a statement of introduction and delay in its pillars. Presenting the semi-sentence on both the verb, the subject and the object, then providing the news of the missing verbs in their name. The research reached a number of findings and recommendations that were proven at its end, and then it was appended by mentioning the sources and references.